Making weight in combat sports - Langan-Evans, C.; Close, G. L.; Morton, J. (Strength and Conditioning Journal, 2011)
Combat sports are categorized into weight classes intended to promote fair competition by matching opponents of equal stature and body mass. Many athletes aim to compete at the lightest weight possible in the belief that it will offer a competitive edge over opponents. Consequently, combat athletes often rely on acute and chronic dehydration and restricted energy intake to make weight. In contrast, this article outlines key principles from exercise metabolism and nutrition that combat athletes can employ to more gradually make weight and therefore avoid the negative health and performance effects associated with traditional weight-making strategies.